Revealing the Attitudes of English Education Students at Indo Global Mandiri University Toward English Language Learning - Debby Falensya; Dio Resta Permana; Desi Surayatika (Departement of Mathematics Education, 2023)
Attitude is currently receiving a lot of attention in learning foreign languages because attitude toward language learning is considered the key factor for people to learn a language. In other words, one part that can indicate the success or failure of learning a foreign language is their attitude toward the language. This study used a descriptive qualitative method and two research instruments, namely closed questionnaires and semi-structured interviews with the research objectives to reveal the attitudes of students of the English education study program at Indo Global Mandiri University toward English language learning and the attitudes of students of the study program English education at Indo Global Mandiri University in each semester. Research participants for the questionnaire were 121 students and 8 students were interviewed. The findings from the questionnaire data analysis revealed that students of the English education study program at Indo Global Mandiri University had a positive attitude toward English language learning and the findings from the interview discovered that students of the English education study program at Indo Global Mandiri University also had a positive attitude in each semester.